The high energy X-ray probe (HEX-P): instrument and mission profile - Madsen, Kristin K.; García, Javier A.; Stern, Daniel; Amini, Rashied; Basso, Stefano; Coutinho, Diogo; Grefenstette, Brian W.; Kenyon, Steven; Moretti, Alberto; Morrissey, Patrick; Nandra, Kirpal; Pareschi, Giovanni; et al. (Frontiers in Astronomy and Space Sciences, 2024)
The High Energy X-ray Probe (HEX-P) is a proposed NASA probe-class mission that combines the power of high angular resolution with a broad X-ray bandpass to provide the necessary leap in capabilities to address the important astrophysical questions of the next decade. HEX-P achieves breakthrough performance by combining technologies developed by experienced international partners. To meet the science goals, the payload consists of a suite of co-aligned X-ray telescopes designed to cover the 0.2 -80 keV bandpass. The High Energy Telescope (HET) has an effective bandpass of 2 -80 keV, and the Low Energy Telescope (LET) has an effective bandpass of 0.2 -20 keV. HEX-P will be launched into L1 to enable high observing efficiency, and the combination of bandpass and high observing efficiency delivers a powerful platform for broad science to serve a wide community. The baseline mission is five years, with 30% of the observing time dedicated to the PI-led program and 70% to a General Observer (GO) program. The GO program will be executed along with the PI-led program.